Improvement of aluminum/polyethylene adhesion through corona discharge. (19th December 2016) - Popelka, Anton; Krupa, Igor; Novák, Igor; Al-Maadeed, Mariam Ali S A; Ouederni, Mabrouk
Abstract: Polyethylene (PE) is often used in several industrial applications including the building, packaging and transport industries. Aluminum (Al) is widely used in different applications in the automotive, railway, aeronautic, and naval industries because of its excellent mechanical and chemical properties. Laminates prepared from Al and PE lead to an enhancement in physical and mechanical properties. These materials play a main role in the packaging and building sectors, such as in TetraPak containers and aluminum composite panels. The main problem observed is associated with the adhesion between polymers and metals. This research focused on investigating the enhancement in the adhesion of the PE/Al laminate using the corona discharge. The corona treatment of the surfaces led to a significant increase in the adhesion of the PE/Al laminate as a result of improved surface properties confirmed by peel test measurements. Moreover, the positive effect of the corona treatment in combination with a primer on the improvement of adhesion characteristics was observed too. Different analytical techniques were employed to characterize the effect of the corona treatment on the improvement in adhesion of PE/Al. A significant increase in wettability was confirmed by the measurement of contact angles. Changes in the surface morphology of the PE and Al surface, after the corona treatments at different operating conditions, were observed using atomic force microscopy (AFM) and scanning electron microscopy (SEM). In addition, x-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) were used to analyze changes in chemical composition after the corona discharge effect on PE and Al surfaces.